The Stranski–Krastanow transition in SiGe epitaxy investigated by scanning transmission electron microscopy. Issue 1 (22nd November 2012) - Walther, Thomas; Norris, David J.; Qiu, Yang; Dobbie, Andrew; Myronov, Maksym; Leadley, David R.
Abstract The Stranski–Krastanow growth mode describes the transition from two‐dimensional flat strained layer epitaxy to the formation of islands that can be technologically used as quantum dots. This has so far been utilized for In(Ga)As/GaAs and Ge/Si heteroepitaxy. Here, we investigate multilayer samples of SiGe alloys grown with different germanium content and thicknesses by reduced pressure chemical vapor phase epitaxy and show that a similar transition can be found in the Si1−xGex‐on‐Si system at x ≈ 0.28. Using a combination of annular dark‐field imaging and energy‐dispersive X‐ray spectroscopy in an analytical transmission electron microscope, we demonstrate that it is the total amount of Ge deposited that determines whether the layers stay flat or roughen, and it is germanium segregation that determines whether and when the transition occurs. While layers with nominally pure Ge roughen at a thickness of ∼0.5 nm, Si1−xGex layers with x ≥ 0.28 stay flat for much longer, until segregated Ge at the surface leads to islanding. Layers below that critical concentration (x ≤ 0.27) can stay flat up to even higher thicknesses, possibly until dislocations will be formed. The critical thickness for the Stranski–Krastanow transition at x = 0.28 is d = 1.7 nm.